The effects of digital cognitive behavioral therapy for insomnia on cognitive function: a randomized controlled trial. Issue 9 (4th March 2020) - Kyle, Simon D; Hurry, Madeleine E D; Emsley, Richard; Marsden, Antonia; Omlin, Ximena; Juss, Amender; Spiegelhalder, Kai; Bisdounis, Lampros; Luik, Annemarie I; Espie, Colin A; Sexton, Claire E
Abstract: Study Objectives: We sought to examine the impact of digital cognitive behavioral therapy (dCBT) for insomnia on both self-reported cognitive impairment and objective cognitive performance. Methods: The Defining the Impact of Sleep improvement on Cognitive Outcomes (DISCO) trial was an online, two-arm, single-blind, randomized clinical trial of dCBT versus wait-list control. Participants were aged 25 years and older, met DSM-5 diagnostic criteria for insomnia disorder, and reported difficulties with concentration or memory. Assessments were carried out online at baseline, and 10 and 24 weeks post-randomization. The primary outcome measure was self-reported cognitive impairment, assessed with the British Columbia Cognitive Complaints Inventory (BC-CCI). Secondary outcomes included tests of cognitive performance, insomnia symptoms, cognitive failures, fatigue, sleepiness, depression, and anxiety. Results: Four hundred and ten participants with insomnia were recruited and assigned to dCBT ( N = 205) or wait-list control ( N = 205). At 10 weeks post-randomization the estimated adjusted mean difference for the BC-CCI was −3.03 (95% CI: −3.60, −2.47; p < 0.0001, d = −0.86), indicating that participants in the dCBT group reported less cognitive impairment than the control group. These effects were maintained at 24 weeks ( d = −0.96) and were mediated, in part, via reductions in insomnia severity and increased sleep efficiency. Treatment effects in favor of dCBT, at both 10 and 24 weeks, were found for insomnia severity, sleep efficiency, cognitive failures, fatigue, sleepiness, depression, and anxiety. We found no between-group differences in objective tests of cognitive performance. Conclusions: Our study shows that dCBT robustly decreases self-reported cognitive impairment at post-treatment and these effects are maintained at 6 months.